The Influence Of Authentic Leadership On Employee Performance Through Employee Involvement At PT Karas Industri Nusa Tenggara Timur - Amaral, Carmelita Maria; Sutoyo; Endriatmoko, Yosa; Zainuddin, Ahmad; Soleha, Siti Nur (PT Maju Malaqbi Makkarana, 2025)
This study aims to examine the influence of authentic leadership on employee performance with employee involvement as a mediating variable at PT Karas Industri, East Nusa Tenggara. Authentic leadership, characterized by transparency, high morality, and healthy relationships between leaders and subordinates, is expected to have a significant impact on improving employee performance. The research method used was quantitative with a survey approach, involving a number of employees of PT Karas Industri as respondents. Data were collected through questionnaires measured using the Likert scale and analyzed with regression analysis techniques to test the relationship between independent variables (authentic leadership) and dependent variables (employee performance), as well as employee engagement as a mediating variable. The results show that authentic leadership has a positive and significant effect on employee performance, and employee engagement mediates this influence substantially. These findings indicate that authentic leaders can improve employee engagement and performance, so it is important for companies to develop this leadership style in order to achieve optimal organizational performance.